Indium Trichloride Catalysed Domino Reactions of Isatin: A Facile Access to the Synthesis of Spiro(indoline-3,4′-pyrano[2,3-c]pyrazol)-2-one Derivatives - Poomathi, Nataraj; Kamalraja, Jayabal; Mayakrishnan, Sivakalai; Muralidharan, D.; Perumal, Paramasivan T. (Synlett, 2014)
A versatile high-yielding indium trichloride mediated one-pot regioselective synthesis of spiroxindoles via domino one-pot, three-component reaction of isatins, pyrazoles, and (E-)-N-methyl-1-(methylthio)-2-nitroethenamine is described. This reaction presumably occurs via domino Knoevenagel condensation–Michael addition–intramolecular O-cyclization sequence. The salient features of the methodology are its clean reaction conditions, the eco-friendly medium, low cost, easy isolation, and excellent yields without column chromatographic purification.
Keywords: domino reaction; spiroxindole; indium trichloride; Michael addition; regioselective synthesis